2018
DOI: 10.1177/1055665618757368
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Evaluation for Safe Le Fort I Osteotomy in Cleft Lip and Palate

Abstract: Our results suggest that the complications of LFI can be reduced in patients with cleft lip and palate by ensuring proper understanding of each patient's maxillary anatomy and bone thickness, as well as the location of the descending palatine artery and the attachment state of the pterygomaxillary junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The first 2 techniques require osteotomy, which can result in complications such as severe postoperative bleeding, inferior alveolar nerve damage, velopharyngeal incompetence, and postsurgical relapse, among others. [19][20][21][22] The TSDO technique applies an external force to the naturally existing cranial and facial sutures. This induces bone reconstruction and new bone formation around the sutures, which can effectively adjust the shape and position of the craniomaxillofacial skeleton to a certain extent without osteotomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first 2 techniques require osteotomy, which can result in complications such as severe postoperative bleeding, inferior alveolar nerve damage, velopharyngeal incompetence, and postsurgical relapse, among others. [19][20][21][22] The TSDO technique applies an external force to the naturally existing cranial and facial sutures. This induces bone reconstruction and new bone formation around the sutures, which can effectively adjust the shape and position of the craniomaxillofacial skeleton to a certain extent without osteotomy.…”
mentioning
confidence: 99%
“…Three main surgical procedures are commonly used in the clinical treatment of midfacial hypoplasia: traditional orthognathic surgical techniques, maxillary distraction with osteotomy, and trans -sutural distraction osteogenesis (TSDO). The first 2 techniques require osteotomy, which can result in complications such as severe postoperative bleeding, inferior alveolar nerve damage, velopharyngeal incompetence, and postsurgical relapse, among others 19–22…”
mentioning
confidence: 99%
“…A common management approach for growing children with CLP is cleft orthognathic surgery, including alveolar bone grafting, orthodontics, and orthognathic surgery such as Le Fort I osteotomy. However, osteotomy has been proven to result in complications such as malocclusion, inferior alveolar nerve damage, inadequate or incomplete splits, postoperative bleeding, velopharyngeal incompetence, and postsurgical relapse 7–10 . Instead, minimally invasive surgeries such as maxillary distraction osteogenesis (DO) have become an advantageous option.…”
mentioning
confidence: 99%
“…However, osteotomy has been proven to result in complications such as malocclusion, inferior alveolar nerve damage, inadequate or incomplete splits, postoperative bleeding, velopharyngeal incompetence, and postsurgical relapse. [7][8][9][10] Instead, minimally invasive surgeries such as maxillary distraction osteogenesis (DO) have become an advantageous option. A study showed that compared with the osteotomy group, the distraction group demonstrated greater maxillary advancement, lesser horizontal relapse of the maxilla, and higher life satisfaction.…”
mentioning
confidence: 99%